Flood prediction using machine learning models - Syeed, Miah Mohammad Asif; Farzana, Maisha; Namir, Ishadie; Ishrar, Ipshita; Nushra, Meherin Hossain (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.